Development of an effective product quality management system - Gritsenko, Nataly; Rud, Elizaveta (Technology audit and production reserves, 2019)
The object of research is product quality management. During the research, the analysis method was used to study approaches to product quality management. The paper reveals the theoretical foundations for product quality management. It is shown that in order to control the quality of products, it is necessary to establish relations between subjects and objects of quality, their changes using the method of a systematic approach. This method shows that for the sustainable economic development of a manufacturing enterprise, first it is necessary to study the structure of the management system. After that, it will be possible to propose an improved control system, schematically depicting it. The international standards proposed in the work will allow the manufacturer to be competitive among others. Producers who seek to export their products must implement in their production a system of measures focused on high product requirements. However, the transition to modern equipment should occur without any psychological discomfort for workers. Do not forget that the use of a quality management system in production is quite long and financially costly. The process of enterprise restructuring should be economically justified, since owners must have income from manufacturing products. That is, the implementation of a quality management system should be cost-effective for a manufacturing enterprise. The use of integrated quality control systems in the modern era of innovation is a sign of enterprise competitiveness. In the work, an improved product quality management system is obtained. This is due to the fact that the proposed system has advantages, in particular, modernization of the material and technical base and employee incentives, not only through material rewards, but also through professional qualifications. Thanks to this, it is possible to obtain new quality indicators. Compared with similar outdated quality methods, the proposed model provides such advantages as the introduction of innovative technologies and equipment in production, training in modern technologies for workers, and allows them to compete in the labor market.